Idiopathic Pulmonary Fibrosis (IPF); Physical, Psychological, social impact on quality of life, and the impact of pulmonary rehabilitation as a mode of palliative care on Physical and Physiological markers - Sameera P. Senanayake (2019)
Background: Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive and life-limiting condition of unknown cause with no curative treatment. The impact of IPF on a patient’s quality of life is devastating, yet relatively little attention has been devoted to understanding the disease from a combined physiological and psychological perspective. There are large gaps in our knowledge of the impact of IPF on the quality of life of patients and, importantly, on the effectiveness of palliative care such as pulmonary rehabilitation (PR) programmes. Methods: We initiated this set of investigations by speaking to ten IPF patients recruited from an IPF support group in Swansea, Wales. The aim of this stage of the study was to understand how patients coped with their initial diagnosis, how they live with the disease day-to-day, their experiences and opinions about the support they receive, and their views on any rehabilitation programmes that they were offered. Semi-structured interviews were conducted and an inductive thematic approach was used to analyse the data, allowing us to identify common themes in the patients’ experiences. In addition, we sought to identify recommendations for practice that could be applied more globally, to add much needed information that might help to enhance the quality of life for IPF patients in the future. Secondly, we quantified the effects of an eight-week PR programme for IPF patients, conducted at Morriston Hospital, Swansea. Fifteen individuals (13 with IPF and two with pulmonary fibrosis associated with rheumatoid disease) underwent physical and physiological assessments during a three-day testing protocol: a) On Day 1, physical function (six-minute walk test) and ventilatory function (spirometry) were measured; b) On Day 2, patients’ cardio-respiratory responses to slowly-increasing, wide-ranging metabolic challenge (using a protocol consisting of periods of rest, incremental bicycle exercise to maximal effort, and post-exercise recovery) were assessed via respiratory gas analysis and ECG recording; c) On Day 3, patients’ cardio-respiratory responses to rapid-onset, high-workload metabolic challenge were assessed (using a protocol including a rapid-onset, constant workload bicycle exercise) by modelling dynamic respiratory oxygen and heart rate responses. Cardiac (RR) interval data were derived from the ECG and used to quantify heart rate variability (HRV) and the cardiac acceleration (AC) and deceleration (DC) capacities (via phase rectified signal averaging, PRSA). Respiratory gas analysis was used to measure the rate of oxygen uptake (V̇O2) and oxygen uptake efficiency slopes (OUES). All assessments were performed before and after participants completed the PR programme. Results:Inductive analysis of interviews identified seven second-order themes and eleven first-order themes, represented by two General Dimensions: ‘Patient experience with the condition’ and ‘Patient-led recommendations for practice’. The key message on ‘coping’ in these patients was that acceptance of their condition led to a sense of optimism. Participants reported using appraisal-focused coping strategies to change their perspectives (thinking positively) and emotion-focused strategies to overcome depression (the main opportunity for emotional expression being an IPF support group). The support group also facilitated problem-focused coping: individuals exchanged knowledge and experience and gave one another tips on how live with their condition. Following the rehabilitation programme, heart rate was elevated by 11-18% during exercise and recovery states. HRV was not statistically influenced by rehabilitation during any stage of the assessment protocol; however, qualitative changes were apparent with HRV increasing by 68-75% during all stages of the protocol. Statistically, AC and DC were similar pre- and post-rehabilitation (AC = -2.7 and -3.2 ms; DC = 2.3 and 3.2 ms, respectively) but again we observed qualitative improvements in these indices of 19% and 38%, respectively.Post-rehabilitation V̇O2 was significantly increased (p=0.01-0.03) during the first two minutes of heavy-intensity exercise, whilst HR was reduced (p=0.04) during this period. OUES and standard measures of respiratory performance (minute ventilation, peak V̇O2) were unchanged following rehabilitation, whilst peak HR and work rates were significantly reduced during incremental exercise only. Conclusion:Health professionals should provide patients with information that focuses on living with IPF, encouraging them to make lifestyle changes and adaptations to improve quality of life. Family members should receive education about IPF so that they can support such changes. Patients should be encouraged to join a support group and to participate in physical activity (again preferably group-based). This study offers novel findings that will help inform much-needed changes in the practice of supporting IPF patients to cope with their diagnosis and disease progression. These studies also provided initial indications that PR programmes might improve heart rate dynamic responses in IPF patients via modulation of the autonomic control of heart rate, even when traditionally-reported respiratory and physical functions are unchanged or diminished. PR also improved the rate of oxygen uptake during heavy-intensity exercise, despite substantially lower heart rates. This suggests that the rehabilitation programme increased systemic arterial-tissue oxygen exchange and/or influenced cardiovascular function to improve systemic oxygen delivery. We might therefore expect that individuals with IPF would find it easier to perform the activities of daily life, including those requiring substantial metabolic demands, following rehabilitation.